The Intersection of Culture and Innovation in Georgian Business - Zhorzholiani, Tinatin (European Scientific Journal, ESJ, 2025)
This paper explores the intersection of culture and innovation within the context of Georgian business, examining how traditional cultural values and modern innovation practices coexist and influence business strategies. The primary aim is to analyze how Georgian businesses incorporate cultural norms while adopting innovative approaches to stay competitive in the global market. The objectives include identifying key cultural factors that shape innovation processes and assessing their impact on business performance. The research employs a mixed-method approach, combining qualitative interviews with business leaders and quantitative analysis of innovation performance metrics across various industries. Results indicate a strong relationship between cultural adaptability and innovative success, with businesses that embrace both traditional Georgian values and modern practices performing better in terms of growth and market adaptability. The findings suggest that cultural identity in Georgia plays a significant role in shaping innovation, providing a unique blend of creativity and tradition that enhances business success. The conclusion emphasizes the importance of balancing cultural heritage with the need for technological advancement to foster sustainable growth.